Going digital? Harnessing social media for employee voice - Dromey, Joe (Birmingham, 2016)
"This report examines the extent to which employers are making use of social media to promote and access employee voice. Social media describes online platforms that allow for user-generated content, interaction and collaboration. It is a relatively new phenomenon, linked to the emergence of ‘web 2.0’ and the move from a static to an interactive internet. This report is largely focused on enterprise social networks. These have the common features of other social media platforms, but they are closed and exclusive, with membership restricted to an individual organisation.